Topographic evolution of tidal flats based on remote sensing: an example in Jiangsu coast, Southern Yellow Sea - Kang, Yanyan; Lei, Jun; Wang, Minjing; Li, Guiping; Ding, Xianrong (Frontiers in Marine Science, 2023)
The topographic evolution of tidal flats is critical for local ecological conservation, coastal zone management, and physical oceanographic studies. However, obtaining this knowledge is often challenging due to the lack of frequently updated topographic data over large areas. With the explosion of remotely sensed data, the waterline method has become the most operational method for tidal flat topography acquisition. In this study, digital elevation models (DEMs) of the tidal flats around Tongzhou Bay on the Jiangsu coast were constructed using the waterline method for three periods (2013, 2015, and 2017) before and after the construction of phase I of the reclamation project. Furthermore, the topographic evolution characteristics were analyzed from four aspects: contours, area changes, erosion–deposition distribution, and typical cross-sections. The results showed that: 1) During the 5 years from 2013 to 2017, the overall tidal flat area (500 km2) of Tongzhou Bay on the Jiangsu coast had been in a state of deposition, with a total siltation thickness of 0.19 m. 2) The reclamation activities affected the topography of the tidal flats quickly, but the recovery was also rapid. During the implementation of the project (in 2015), the area of the tidal flats above the −2-m contour was rapidly reduced by 20 km2 but rapidly recovered to the pre-project level after the completion of the project (in 2017). 3) The reclamation project directly affected the distribution of erosion and siltation. Outside the seawall on the east side of the Yaosha sand ridge, the 0-m contour expanded rapidly to the outer sea, reaching more than 250 m/year. 4) The sandbars in Tongzhou Bay on the Jiangsu coast generally had a southward-moving trend. Over the past 40 years, the Yaosha sand ridge had shifted southward by 2,500 m and the Lengjiasha sand ridge by more than 5,000 m. This study provides a remote sensing solution for the topographic evolution of large tidal flats under the influence of human reclamation activities.